Ancient and Famous Trees Risk Assessment in Changting Based with Multi-Level and Multi-Dimensional Indicator System. Issue 2 (March 2021) - Lan, Yuxiang; Lin, Yingfang; Liu, Fan; Chen, Han; Li, Junyi; Chen, Ye; Dong, Jianwen
Abstract: According to the results of the second census of ancient and famous trees and field investigation in Changting County, Through VTA method and AHP method, the multi-level and multi-dimensional evaluation index system of risk degree of ancient and famous trees was constructed. The results show that: The higher weight of growth factors are the main trunk diseases and insect pests, abnormal cracks in the main trunk, hollow trunk, branch diseases and insect pests, abnormal cracks in the branches, dangerous dead branches, root diseases and insect pests, leaf diseases and insect pests. The growth space of tree roots is the most important factor in environmental factors. Among the anthropogenic factors, the most important ones are the artificial dumping of pollutants and the lack of professional management. Hazard index of Taxus chinensis var. mairei is maximum, followed by Schima superba, Cinnamomum camphora and Liquidambar formosana . The most dangerous indicators are the professional level of managers, lack of professional management, V-angle trunk and plant parasitism. Through the risk assessment, this paper seeks for the key points of management and protection of ancient and famous trees, aims at solving problems and reducing the risk of ancient and famous trees, so as to promote the management and protection of ancient and famous trees.